CLINICAL CASE OF SEVERE DISSEMINATED EXTRAPULMONARY TUBERCULOSIS - S. Yu. Shevchenko; E. V. Kulchavenya; D. P. Kholtobin; V. T. Khomyakov; E. V. Brizhatyuk (Туберкулез и болезни лёгких)
The article presents the clinical case when the patient was admitted to Novosibirsk Tuberculosis Research Institute, Russian Ministry of Health, in September 2013 from the territory supervised by the institute (Sakha Republic) with the advanced form of generalized urogenital tuberculosis, complicated by terminal renal failure and tuberculosis colitis. The patient had been treated for urogenital infections - veiled manifestations of tuberculosis, with no success for 10 years, he underwent a number of surgeries. Tuberculosis was diagnosed histologically when intestine fistula developed.